PENGARUH KEBIASAAN SELF-REWARD TERHADAP KONDISI KEUANGAN PRIBADI MAHASISWA - Olivia Renata; Atika Kahla Nazori; Nyimas Khansa Nisrina Auditra; Alya Zahirah Handayani; Sriayu Wulandari Sufansya (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to determine the influence of self-reward habits on students’ personal financial behavior. The phenomenon of self-reward is commonly found among young adults, particularly university students who often give themselves rewards after completing assignments, exams, or specific tasks. However, this habit may affect personal financial management when practiced without proper planning. The research employed a quantitative method with a descriptive associative approach. Data were collected through questionnaires distributed to 30 active students at Sriwijaya University. The data were analyzed using a simple linear regression test. The results indicate that self-reward has a positive and significant effect on students’ personal financial behavior. The more frequently students engage in self-reward, the higher their tendency to exhibit consumptive behavior and lack planning in managing their finances.